Statins in Primary Prevention in People Over 80 Years - Marcellaud, Elodie; Jost, Jeremy; Tchalla, Achille; Magne, Julien; Aboyans, Victor (The American journal of cardiology, 2023)
In the much older population (≥80 years), the management of cardiovascular diseases requires specific research to avoid a plain transposition of medical practice from younger populations. Whether statins are useful in primary prevention in this population is not clear. The 3 intricate issues requiring attention are (1) the impact of hypercholesterolemia on mortality and major adverse cardiovascular events in subjects >80 years, (2) the efficacy of statins to prevent cardiovascular events at this age, and (3) the safety and tolerance of statins in this population. Three systematic reviews were performed using a search on EMBASE, MEDLINE, Cochrane Central Register of Controlled Trials, and Web of Science databases including publication until January 2021. Among the 7,617 references identified, 29 were finally retained. Regarding the first objective (16 studies, 121,250 participants), 7 studies (10,241 participants) did not find total cholesterol and low-density lipoprotein levels associated with an increased rate of major cardiovascular events in octogenarians. A total of 6 studies (14,493 participants) found increased levels associated with events, whereas 3 studies (96,516 participants) found the opposite, with increased risk of major adverse cardiovascular events with lower levels of cholesterol. In 8 studies (436,005 participants) addressing the efficacy of statins, most did not indicate a significant decrease in the rate of major cardiovascular events in these subjects. Finally, regarding tolerance (9 studies, 217,088 participants), the most important side effects in this population were muscular, hepatic, and gastrointestinal disorders. These events were more frequent than in the younger population. In conclusion, in the absence of convincing evidence, the benefit of statins in primary prevention for much older patients is not certain. Their prescription in this setting should only be considered case by case, taking into consideration physiological status, co-morbidities, level of risk, and expected life expectancy. Specific trials are mandatory.